Dampak Revitalisasi Kawasan Pesisir Ampenan terhadap Sosial-Ekonomi Berdasarkan Pengetahuan Masyarakat Pesisir Ampenan - Ahmad Jupri; Hilman Ahyadi; Pahmi Husain; Moh Nurkholis Rifwan; Baiq Anggun Yuliandini; Dea Dina Mutia; Aulia Khaerunnisa; Hardi Arya Pratama; Ahmad Saddam Khazimi; Bening Sagita Lestari; Misrahul Aola; Rohyani Rohyani; Nuraema Sintia; Nurul Hidayah (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Coastal area revitalization is an effort to organize the area that aims to improve the quality of the environment and encourage the social and economic development of the community. This study aims to analyze the impact of the revitalization of the Ampenan Coastal Area, Mataram City, on the socio-economic conditions of the community based on the perceptions and experiences of the local community. The study uses a descriptive quantitative approach with data collection techniques through observation, interviews, questionnaires, and documentation. A total of 30 respondents consisting of traders, parking attendants, visitors, and local residents were selected using an accidental sampling technique. The data were analyzed descriptively to describe socio-economic changes, while changes in community income before and after revitalization were tested using a paired sample t-test. The results showed that revitalization had a positive impact on improving environmental quality, economic activity, and the number of tourist visits. The average community income increased by 86.9% per day after revitalization, and the results of the paired sample t-test showed a significant difference between income before and after revitalization (p < 0.05). However, the area revitalization also caused some traders to lose business space due to limited stalls in the new system. Thus, the revitalization of the Ampenan Coastal Area contributes to improving the socio-economic conditions of the community, although more inclusive policies are needed to ensure that the benefits of development are felt equally by all coastal community groups.